Disaster health education framework for short and intermediate training in Saudi Arabia: A scoping review - Nidaa Bajow; Luc J. M. Mortelmans; Nisreen Maghraby; Salem Ali Alatef Sultan; Zakaria A. Mani; Zakaria A. Mani; Samer Aloraifi (Frontiers Media S.A., 2022)
BackgroundSaudi Arabia has made extensive efforts to manage disasters using unique national approaches; however, challenges and obstacles concerning disaster health handling persist. The nation has a reactive strategy to disaster management with a need for increased involvement of health professionals in disaster management and improvement of healthcare facilities emergency preparedness including competency-based education training.ObjectiveA comprehensive and consistent approach of disaster education programs for short and intermediate training of health professionals involved in disaster responses in Saudi Arabia is still not evident. Therefore, it is vital to explore and map the current state of the disaster education framework in Saudi Arabia.MethodsThe Joanna Briggs Institute approach for scoping reviews was used to assess research articles and preprints between January 2000 and September 2021 from Saudi Digital Library; PubMed, CINAHL, and Google Scholar. Five experts identified key aspects of the disaster education approach and eligibility criteria to facilitate identification of relevant articles.ResultsOnly five articles met the specified criteria and described two short and three intermediate courses on disaster health management in Saudi Arabia. All courses involved competency-specific training aimed at basic or foundational level and involved a range of activities and learning types. None had refresher courses within 12 months.ConclusionThe review highlights the obvious scarcity of short and intermediate term evidence-based disaster health programs in Saudi Arabia. Adoption of the education framework proposed by the authors based on international frameworks could improve the quality and consistency of the disaster education curriculum in Saudi Arabia.